2010
DOI: 10.2178/jsl/1268917492
|View full text |Cite
|
Sign up to set email alerts
|

Schnorr trivial sets and truth-table reducibility

Abstract: We give several characterizations of Schnorr trivial sets, including a new lowness notion for Schnorr triviality based on truth-table reducibility. These characterizations allow us to see not only that some natural classes of sets, including maximal sets, are composed entirely of Schnorr trivials, but also that the Schnorr trivial sets form an ideal in the truth-table degrees but not the weak truth-table degrees. This answers a question of Downey. Griffiths and LaForte.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 15 publications
0
39
0
Order By: Relevance
“…Kjos-Hanssen et al [14] strengthened this equivalence to the equivalence between two reducibility of ≤ LR and ≤ LK . By the results in Franklin and Stephan [10] and Miyabe [18], lowness for uniformly computable measure machines and lowness for uniform Schnorr randomness are euiqvalent. Then we strengthned this equivalence to the equivalence between reducibilities.…”
Section: Preorderings Related To Uniform Schnorr Randomnessmentioning
confidence: 91%
See 4 more Smart Citations
“…Kjos-Hanssen et al [14] strengthened this equivalence to the equivalence between two reducibility of ≤ LR and ≤ LK . By the results in Franklin and Stephan [10] and Miyabe [18], lowness for uniformly computable measure machines and lowness for uniform Schnorr randomness are euiqvalent. Then we strengthned this equivalence to the equivalence between reducibilities.…”
Section: Preorderings Related To Uniform Schnorr Randomnessmentioning
confidence: 91%
“…We refer to [24,3,4,25] for computability from 2 ω to τ , from 2 ω to R and so on. Miyabe and Rute [19] showed that uniform Schnorr randomness is equivalent to tt-Schnorr randomness studied in [10,18].…”
Section: Definition 22mentioning
confidence: 99%
See 3 more Smart Citations